Clinical-grade human skin-derived ABCB5+ mesenchymal stromal cells exert anti-apoptotic and anti-inflammatory effects in vitro and modulate mRNA expression in a cisplatin-induced kidney injury murine model - Rendra, Erika; Crigna, Adriana Torres; Daniele, Cristina; Sticht, Carsten; Cueppers, Maike; Kluth, Mark Andreas; Ganss, Christoph; Frank, Markus H.; Gretz, Norbert; Bieback, Karen (Frontiers in Immunology, 2024)
Acute kidney injury (AKI) is characterized by a rapid reduction in renal function and glomerular filtration rate (GFR). The broadly used anti-cancer chemotherapeutic agent cisplatin often induces AKI as an adverse drug side effect. Therapies targeted at the reversal of AKI and its potential progression to chronic kidney disease or end-stage renal disease are currently insufficiently effective. Mesenchymal stromal cells (MSCs) possess diverse immunomodulatory properties that confer upon them significant therapeutic potential for the treatment of diverse inflammatory disorders. Human dermal MSCs expressing ATP-Binding Cassette member B5 (ABCB5) have shown therapeutic efficacy in clinical trials in chronic skin wounds or recessive dystrophic epidermolysis bullosa. In preclinical studies, ABCB5+ MSCs have also shown to reverse metabolic reprogramming in polycystic kidney cells, suggesting a capacity for this cell subset to improve also organ function in kidney diseases. Here, we aimed to explore the therapeutic capacity of ABCB5+ MSCs to improve renal function in a preclinical rat model of cisplatin-induced AKI.First, ABCB5+ MSCs suppressed cisplatin-induced apoptosis of human conditionally-immortalized proximal tubular epithelial cells in vitro, most likely by reducing oxidative stress. Second, ABCB5+ MSCs inhibited the proliferation of either human or rat peripheral blood mononuclear cells, in the human system via the Indoleamine/kynurenine axis and in the murine context via nitric oxide/nitrite. Third, ABCB5+ MSCs decreased TNF-α secretion after lipopolysaccharide stimulation and modulated phagocytosis and in both human and rat macrophages, involving prostaglandin E2 and TGF-β1, respectively. Fourth, clinical-grade ABCB5+ MSCs grafted intravenously and intraperitoneally to a cisplatin-induced AKI murine model exerted modulatory effects on mRNA expression patterns towards an anti-inflammatory and pro-regenerative state despite an apparent lack of amelioration of renal damage at physiologic, metabolic, and histologic levels.Our results demonstrate anti-inflammatory and pro-regenerative effects of clinical grade ABCB5+ MSCs in vitro and in vivo and suggest potential therapeutic utility of this cell population for treatment or prevention of cisplatin chemotherapy-induced tissue toxicity.